2018
DOI: 10.1016/j.jssr.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating a mindset of civic engagement among young adolescents

Abstract: This study explored early stages of civic engagement among 48 young adolescents by examining what they think about as a result of participating in various civic learning activities during a summer civics camp, and whether or not this thinking varied based on participants’ entering civic profiles. Participant thinking was assessed through concept maps. Based on survey data, participants were classified into entering profiles of civic development: justice-oriented or participatory youth; civically purposeful or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 23 publications
2
3
0
Order By: Relevance
“…These findings are consistent with those of other authors who argue that civic skills promote the development of individuals to acquire critical skills that are essential for adulthood (Forestiere, 2015;Shiller, 2013;Quinn & Bauml, 2018). When students do not engage in civic activities, they have fewer opportunities to develop relevant skills such as leadership skills, interpersonal interaction skills, critical thinking skills and community mobilization skills.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These findings are consistent with those of other authors who argue that civic skills promote the development of individuals to acquire critical skills that are essential for adulthood (Forestiere, 2015;Shiller, 2013;Quinn & Bauml, 2018). When students do not engage in civic activities, they have fewer opportunities to develop relevant skills such as leadership skills, interpersonal interaction skills, critical thinking skills and community mobilization skills.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous research findings, this study revealed that the civic knowledge of students is derived from: active scholarly engagement (Fitzgerald et al, 2016); engagement opportunities (Hylton, 2018); extra-curricular activities (Quinn & Bauml, 2018) and information received from other people. Lenzi and others (2014) contribute to the debate on campus civic climate by arguing that when students perceive high levels of democratic and open climate in their institutions, they willingly express their opinion on social issues and their motivation to support activities that are aimed at resolving societal problem is increased.…”
Section: Discussionsupporting
confidence: 89%
“…However, theoretically and empirically, existing research does support a connection between early purpose development and the empathy that young adolescents feel in responses to suffering they see or about which they learn (Malin et al, 2015, 2017). In addition, there is no question that young adolescents are capable of demonstrating the various dimensions of civic purpose, and many, if not most, do demonstrate aspects of at least one dimension of purpose (e.g., holding future aspirations, finding an activity meaningful, acting to accomplish a BTS goal; Malin et al, 2017; Quinn & Bauml, 2018).…”
Section: Civic Purpose As a Construct For Studying Civic Developmentmentioning
confidence: 99%
“…In 2013, the authors developed and implemented a free, weeklong summer civics institute for 5-9th graders called iEngage (pseudonym). iEngage has continued each summer since 2013. iEngage is an out-of-school action civics program that seeks to develop young people's civic and political competence and strengthen their community and political engagement through inquiry-based civics projects in which they research and act upon local community issues Blevins, LeCompte, & Wells, 2016;, 2016, LeCompte, Blevins, & Ray, 2017, Quinn & Bauml, 2018. The institute utilizes an action civics model to foster participants' understanding of and engagement in civic life (Levinson, 2014;Pope, Stolte, & Cohen, 2011).…”
Section: Iengage Summer Civics Institutementioning
confidence: 99%